Stochastic Tension‐Stiffening Approach for the Solution of Serviceability Problems in Reinforced Concrete: Exploration of Predictive Capacity. (24th November 2015) - Gribniak, Viktor; Mang, Herbert Anton; Kupliauskas, Rimantas; Kaklauskas, Gintaris; Juozapaitis, Algirdas
Abstract: Dealing with short‐term deformations and the tension‐stiffening effect in reinforced concrete (RC), the current study consists of two parts as presented in two separate manuscripts. Based on the test data of more than 300 RC ties, alternative tension‐stiffening relationships of different complexity were proposed in the first article (Part I). In the companion manuscript (Part II), a stochastic modeling technique for assessing the deformation response of RC elements, subjected to different combinations of tension and flexure, is proposed. Based on stochastic principles, this technique allows not only to predict the average deformation response, but also to establish bounds of these predictions that are of vital importance for practical problems. The proposed technique is verified with the help of independent test data in order to validate the accuracy of the predictions of deformation, using the tension‐stiffening models proposed in Part I of the article. Test specimens with different arrangements of steel or GFRP bars in the tensile zone were considered. The analysis has revealed that the influence of the degree of sophistication of the tension‐stiffening models on the analysis results is smaller than the one of an adequate assessment of the shrinkage effect. The prediction accuracy is also related to the specific arrangement of reinforcement.